The Effect of Daily Uplift, Daily Hassles, Family Support Against Well-Being Through Work Engagement - Hardiyatno, Wahyu Panji; Tanuwijaya, Justine; Gunawan, Andreas Wahyu (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This research aims to determine and analyze the influence of daily uplift, daily hassles, and family support on well-being which is mediated by work engagement. The research method used is quantitative research by testing the validity of the variables daily uplift, daily hassles, and family support towards well-being mediated by work engagement in a service industry. This research uses independent variables including daily uplift, daily hassles, and family support. Meanwhile, the dependent variable includes well-being and there is an intervening variable or mediating variable between the two previous variables, namely work engagement. To find out and analyze the relationship between these variables, the author uses the latest version of SPSS Statistical Data Processing calculations and AMOS 24 Data Processing calculations. The research results show that there is a positive and significant influence between the influence of daily uplift and family support on well-being which is mediated by work engagement. On the other hand, the constant presence of daily hassles does not have a significant effect on well-being which is mediated by work engagement. This research implies that it is hoped that human resource management will be able to minimize daily hassles that occur continuously because they have a negative impact on the employees concerned and also on the progress of the company.